2012
DOI: 10.3171/2012.1.jns111313
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-derived versus pressure wave amplitude–derived indices of cerebrovascular pressure reactivity in relation to early clinical state and 12-month outcome following aneurysmal subarachnoid hemorrhage

Abstract: ObjectIndices of cerebrovascular pressure reactivity (CPR) represent surrogate markers of cerebral autoregulation. Given that intracranial pressure (ICP) wave amplitude–guided management, as compared with static ICP-guided management, improves outcome following aneurysmal subarachnoid hemorrhage (SAH), indices of CPR derived from pressure wave amplitudes should be further explored. This study was undertaken to investigate the value of CPR indices derived from static I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 50 publications
0
30
0
2
Order By: Relevance
“…Evaluation of cerebral autoregulation is being increasingly recognised as a factor requiring consideration in the management of patients with SAH 112 114 113 162–164. Three recent prospective studies have demonstrated that indirect indices of cerebral autoregulation can be used to prognosticate DCI as well as long-term outcome after SAH 112 113 163 164 165. Importantly, autoregulation was found to deteriorate before clinical symptoms as well as radiographically identifiable arterial narrowing 163.…”
Section: Cerebral Autoregulationmentioning
confidence: 99%
“…Evaluation of cerebral autoregulation is being increasingly recognised as a factor requiring consideration in the management of patients with SAH 112 114 113 162–164. Three recent prospective studies have demonstrated that indirect indices of cerebral autoregulation can be used to prognosticate DCI as well as long-term outcome after SAH 112 113 163 164 165. Importantly, autoregulation was found to deteriorate before clinical symptoms as well as radiographically identifiable arterial narrowing 163.…”
Section: Cerebral Autoregulationmentioning
confidence: 99%
“…PRx is an autoregulatory index that relies on the correlation between spontaneous fluctuations in mean arterial blood pressure (MAP) and intracranial pressure (ICP). PRx has been studied extensively in traumatic brain injury (TBI) and to some extent also in SAH [2, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…The management goal is then to keep the mean ICP <20-25 mmHg [1,7], or the mean ICP wave amplitude (MWA) <5 mmHg [5]. In an attempt to characterize the intracranial pressure-volume compensatory reserve capacity some authors have in addition calculated ICP-derived indices [6,8,9]. An index measuring the correlation coefficient (R) between the ICP wave amplitude (A) and the mean ICP (P) level (referred to as RAP) has thus been applied in the surveillance of patient groups such as those suffering from traumatic brain injury (TBI), cerebral bleeds or hydrocephalus [8,10-12].…”
Section: Introductionmentioning
confidence: 99%